THE EFFECTIVENESS OF GIST (GENERATING INTERACTIONS BETWEEN SCHEMATA AND TEXT) AND KWL (KNOW, WANT, AND LEARNED) STRATEGIES TO IMPROVE READING ACHIEVEMENT OF MALE AND FEMALE STUDENTS (Universitas Negeri Semarang, 2015)
This study is an experimental research with a factorial design which aimed to find out the effectiveness of GIST and KWL strategies to improve reading achievement of male and female students. The samples of the study were the eleventh students of Senior High School 2 Demak in the academic year of 2014/2015. There were two classes, the first and the second experimental groups. GIST strategy was used in the first experimental group, and KWL strategy was used in the second experimental group. To answer research questions number one up to five, T-test was used. While two-ways ANOVA with F-test at the 5% (0.05) level of significance was used to answer the fifth up to seventh question. The result of this study showed that GIST and KWL strategies are effective to improve reading achievement of male and female students. In additon, there is no significant difference of the use of GIST and KWL strategies to improve reading achievement of male and female students. Futhermore, there is no significant difference of gender in using GIST and KWL strategies to improve reading achievement. Finally, there is no interaction among GIST, and KWL strategies, reading achievement, and gender.